The posttraumatic impact of recurrent pregnancy loss in both women and men - Kuhlmann, Emily; Scharli, Pauline; Schick, Maren; Ditzen, Beate; Langer, Laila; Strowitzki, Thomas; Wischmann, Tewes; Kuon, Ruben-Jeremias (Geburtshilfe und Frauenheilkunde, 2023)
Recurrent pregnancy loss is usually associated with significant psychological distress for both partners of the couple. It may act as a traumatic experience resulting in a posttraumatic stress disorder. The object of this study is to examine the posttraumatic impact of recurrent pregnancy loss on men and women and their interdependencies.
Gesehen am 19.01.2024